Çocukluk çağında osteosarkom - EKER, NURŞAH (Türkiye Klinikleri Yayınevi, 2021)
Osteosarkom çocukluk çağında en sık görülen primer malign kemik tümörüdür. Kemik dokudan köken alan, genellikle yüksek grade, uzak metastaz potansiyeli olan ve tedavi edilmez ise kötü prognoz ile seyreden tümörlerdir. Osteosarkom tedavisi, multidisipliner bir tedavi yönetimini içermektedir. Ana tedavi modelitesi, neoadjuvant ve adjuvant kemoterapi ile birlikte cerrahi eksizyon ve radyorezistan bir tümör olmasına rağmen seçilmiş vakalarda yüksek doz radyoterapidir. Günümüzde, hala standart olarak YD-MTX, sisplatin ve doxorubicinden oluşan üçlü multiajan tedavi önerilmektedir. Lokalize hastalık sonrası %30-40 oranında relaps hastalık görülmektedir. Relaps hastalıkta cerrahi tedavi önemini korumakta olup, kemoterapi için standart bir yaklaşım yoktur. Relaps/refrakter hastalıkta prognoz kötüdür ve sağ kalımı arttırmak için yeni nesil tedavi ajanlarına ihtiyaç vardır.

Osteosarcoma is the most common primary malignant bone tumor in childhood. They are tumors originating from the bone tissue, usually with high grade, distant metastasis potential and with poor prognosis if left untreated. Osteosarcoma treatment includes a multidisciplinary treatment management. The main treatment modality is surgical excision with neoadjuvant and adjuvant chemotherapy and high-dose radiotherapy in selected cases, although it is a radioresistant tumor. Nowadays, triple multiagent therapy consisting of HD-MTX, cisplatin and doxorubicin is still recommended as standard. After localized disease, relapsed disease is seen at a rate of 30-40%. Surgical treatment maintains its importance in relapsed disease, and there is no standard approach for chemotherapy. Prognosis is poor in relapsed/refractory disease and new generation treatment agents are needed to increase survival.
Osteosarcoma in childhood
Keywords: Osteosarkom; çocuk; tedavi; Osteosarcoma; pediatric; treatment